2018
DOI: 10.14744/nci.2017.54036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long Term Computure Use on Dry eye

Abstract: OBJECTIVE: To evaluate the effects of long-term computer use on tear production and evaporation. METHODS: In this study, 30 eyes of 30 people using computer for 8 hours a day were taken as the study group. In the control group, 30 eyes of 30 healthy individuals who did not spend 1 hour using computer on a daily basis were evaluated. The cases were examined at 8 am and 5 pm. The Schirmer test, tear break-up time (TBUT), and ocular surface disease index (OSDI) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 13 publications
(14 reference statements)
5
59
1
2
Order By: Relevance
“…Furthermore, Akkaya et al [ 26 ] described a comparable finding to this study where DED symptoms increase with prolonged daily electronic device usage. Among the different eye procedures, LASIK and cataract surgeries were the most procedures known to result in transient DED as reported in the literature [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, Akkaya et al [ 26 ] described a comparable finding to this study where DED symptoms increase with prolonged daily electronic device usage. Among the different eye procedures, LASIK and cataract surgeries were the most procedures known to result in transient DED as reported in the literature [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Descriptive analysis based on frequency and percent distribution was done for patient's characteristics, eye care, and depression severity. Regarding PHQ-9, the total score for the different items was summed and categorized into no depression (zero score), minimal depression (1-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), moderately severe depression (15)(16)(17)(18)(19), and severe depression (20)(21)(22)(23)(24)(25)(26)(27). Cross-tabulation was used to assess the relationship between personal data and depression and between eye care and dry eye data with different items including contact lens use, daily screen time.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained in another study performed by Büyükbaş et al 8 , Yazici et al 16 and Bayhan et al 18 reported significantly higher OSDI scores in those with 7-8 hours of computer use daily compared to those with less than 1 hour per day. Although Akkaya et al 19 observed similar OSDI scores in individuals with average daily computer use of 7 hours and less than 1 hour, they noted a difference in their tear breakup times and reported that dry eye developed in the heavier computer users due to excessive tear evaporation. In the current study, half of the participants had OSDI scores indicating moderate/severe ocular surface disease and a significant positive correlation was detected between OSDI score and daily duration of computer use.…”
Section: Discussionmentioning
confidence: 96%
“…Digital eye strain is a manifestation of evaporative dry eye[ 7 ] caused by decreased and incomplete blink rate leading to ocular surface compromise, and asthenopic symptoms[ 8 ] caused by a visual system in a constant state of accommodation and convergence. Other environmental factors, such as poor ergonomics, improper lighting, glare, decreased humidity in air-conditioned rooms,[ 9 ] are all contributing factors for worsening of these symptoms.…”
Section: Pathophysiology Of Digital Eye Strainmentioning
confidence: 99%